2008
DOI: 10.1097/aud.0b013e31816a0d3d
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical Versus Physiological Spatial Forward Masking and the Relation to Speech Perception in Cochlear Implants

Abstract: Objectives-The primary goal of this study was to determine if physiological forward-masking patterns in cochlear implants are predictive of psychophysical forward-masking patterns (PFM). It was hypothesized that the normalized amount of physiological masking would be positively correlated with the normalized amount of psychophysical masking for different masker-probe electrode separations. A secondary goal was to examine the relation between the spatial forwardmasking patterns and speech-perception performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 57 publications
3
83
4
2
Order By: Relevance
“…Because ECAPs generally require higher current levels to evoke a response, there can be greater spread of excitation in the cochlea compared with lower current levels for psychophysical tasks. A study by Hughes and Stille (2008), using a forward-masking paradigm, showed that excitation patterns for ECAP measures were broader than those obtained for psychophysical (pulsetrain) measures. Therefore, the ECAP may be less sensitive for measuring overlap of neural excitation patterns produced by relatively high-level stimulation of closely spaced electrodes such as adjacent physical electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Because ECAPs generally require higher current levels to evoke a response, there can be greater spread of excitation in the cochlea compared with lower current levels for psychophysical tasks. A study by Hughes and Stille (2008), using a forward-masking paradigm, showed that excitation patterns for ECAP measures were broader than those obtained for psychophysical (pulsetrain) measures. Therefore, the ECAP may be less sensitive for measuring overlap of neural excitation patterns produced by relatively high-level stimulation of closely spaced electrodes such as adjacent physical electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…The ECAP SOE function reflects the neural excitation pattern elicited by a probe electrode resolved using a forward-masking paradigm. It has been shown that neural excitation measured by the ECAP SOE is comparable to that measured psychophysically using a forward-masking paradigm (Cohen et al, 2003;Hughes and Stille, 2008). In Hughes and Abbas (2006a), the width of the SOE function (calculated as 75% of the normalized amplitude) was compared to the slope of the electrode pitchranking (2IFC) function in ten subjects.…”
Section: Introductionmentioning
confidence: 99%
“…A more straightforward way to explain the variable perceptual data is to directly estimate the excitation patterns of steered pTP stimuli with different α in each subject. This can be achieved by measuring the forward masking patterns of steered pTP stimuli using psychophysical methods (e.g., Chatterjee and Shannon 1998; Kwon and van den Honert 2006b; Srinivasan et al 2010;Landsberger et al 2012) or using electrically evoked compound action potentials (e.g., Cohen et al 2003;Hughes and Stille 2008).…”
Section: General Discussion and Summarymentioning
confidence: 99%